2017
DOI: 10.1371/journal.pone.0182239
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety, and smartphone addiction in university students- A cross sectional study

Abstract: ObjectivesThe study aims to assess prevalence of smartphone addiction symptoms, and to ascertain whether depression or anxiety, independently, contributes to smartphone addiction level among a sample of Lebanese university students, while adjusting simultaneously for important sociodemographic, academic, lifestyle, personality trait, and smartphone-related variables.MethodsA random sample of 688 undergraduate university students (mean age = 20.64 ±1.88 years; 53% men) completed a survey composed of a) question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

49
315
8
30

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 436 publications
(458 citation statements)
references
References 19 publications
49
315
8
30
Order By: Relevance
“…A systematic review of 23 peer reviewed papers reported that depression was consistently related to problematic smartphone usage [22]. Depression in Lebanese and Austrian university students was also significantly associated with smartphone addiction [12, 23] or problematic mobile phone usage [13] respectively. In fact, one of the predisposing factors of smart phone addiction is increased stress levels followed by a decrease in self-control, which eventually leads to the over usage of smartphones [24].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of 23 peer reviewed papers reported that depression was consistently related to problematic smartphone usage [22]. Depression in Lebanese and Austrian university students was also significantly associated with smartphone addiction [12, 23] or problematic mobile phone usage [13] respectively. In fact, one of the predisposing factors of smart phone addiction is increased stress levels followed by a decrease in self-control, which eventually leads to the over usage of smartphones [24].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of male students, male heavy internet users favoring online games had lower average academic grades than male non-heavy users and those who especially favor information seeking and chatting (Chen & Tzeng, 2010). Previous research showed that smartphone and internet addiction were significantly associated with alcohol abuse, depression and anxiety Matar Boumosleh & Jaalouk, 2017), poor sleep quality (Zhang et al, 2017), and quality of life . These adverse health outcomes have a negative impact on academic studies.…”
mentioning
confidence: 94%
“…It has been suggested that excessive internet use could represent addictive behavior with mental health implications. [1][2][3] In tandem with the splurge in access to the Internet globally, with the rise of new-generation gadgets, the risk of "internet addiction" is emerging as a significant behavioral addiction pandemic to be tackled worldwide.…”
Section: Introductionmentioning
confidence: 99%